Effect of biomass Azolla microphylla on chemical parameters of water quality in peat soil medias - Eko Candra; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on April-May 2018 in the Kualu Nenas Village, Tambang District, Kampar regency, Riau Province. Objective of study was to determine the effect of different biomass A. microphylla on increasing chemical parameters of water on peat soil. The method used in this study is an experimental method using a Complete Random Design (CRD) with 1 factor, 4 treatments and 5 replications. The treatment used in this experiment are P0 (without biomass of Azolla michrophylla ), P1 (biomass Azolla michrophylla 20 g/m2), P2 (biomass Azolla michrophylla 40 g/m2) and P3 ( biomass Azolla michrophylla 60 g/m2). The water quality parameters measured in this study are, pH, dissolved oxygen, CO2, nitrate and phosphate.The results showed that biomass of Azolla microphylla had a significantly different effect on changes in chemical parameters of water on peat soil media. The best results that can improve the chemical parameters of peat water are found in the treatment of Azolla michrophylla 20 g / m2 (P1) by increasing the pH value (6.2); Dissolved oxygen (6,64 mg/L); Nitrate (17,72 mg/L) and phosphate (3,31 mg/L). Except for CO2 concentration found in treatment P3 (Use of bimasa A. michrophylla 60 g / m2) which is 21.9 mg / L. Keyword : Azolla michrophylla, chemical parameters, Peat soil